Friday night lights [videorecording (DVD)] - Berg, Peter, 1964-; Cohen, David Aaron; Thornton, Billy Bob; Luke, Derek, 1974-; Hernandez, Jay, 1978-; Black, Lucas, 1982-; Hedlund, Garrett, 1985-; McGraw, Tim; Bissinger, Buzz, 1954- (Universal, 2004)
Odessa is an oil town in the western part of Texas that is home to the Permian High School Panthers, the football team with the best winning record. The city's economy is in a tailspin, but football is the one thing that brings all the people of Odessa together, and on Friday nights, as many as 20,000 people fill Permian's football stadium to watch Coach Gary Gaines lead the team to victory. And in Odessa, a football victory is prized above all else. The players ponder the fact that a championship season can be as much a burden as a triumph.